Include the knowledge economy skills in the biology book of the basic stage in Jordan - qublan, Ahmed Barham (Journal of Educational and Psychological Sciences, 2020)
The aim of this study is to investigate the degree of inclusion of the biology textbooks for the basic stage (ninth and tenth elementary) in the academic year (2018/2019) in Jordan for the skills of the knowledge economy and to reveal their degree of respect for the principles of the knowledge economy, so the researcher used the analytical description. The study sample was respect the community research and was composed of the biology books of the basic stage (ninth and tenth basic) in the academic year (2018/2019) in Jordan. To achieve that the researcher used tool consists of (38) skill, to measure knowledge economy skills included in four fields. The study concluded that the technological field was ranked first with 32%, followed by the social field with 30%, in an acceptable and logical response. The economic field and the cognitive field they have a low level of curriculum with 21% and 17% respectively. The results show that the tenth elementary book was higher than ninth elementary book in all skills except the skills of technological field was slightly difference to ninth grade. The results showed that the tenth grade was more fortunate in the skills of all fields, except the technology skills domain were tends to ninth grade with slightly difference.
Keywords: knowledge economy; biology book; upper elementary stage